Developing Oral Tradition-Based Digital Islamic Cultural History Learning in Elementary Schools: The ChronoLearn Media - Niam, Ahmad Ulin; Jakak, Pamuji M; Daryanti, Aan; Ansori, Tony (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning Islamic Cultural History faces challenges in student motivation and limited instructional media. This study aims to develop ChronoLearn, an interactive digital e-historical book integrating Komering oral traditions to support elementary-level learning. The research employed a development approach using the ADDIE model, limited to the stages of analysis, design, and development, without proceeding to implementation and evaluation. ChronoLearn was designed as an interactive digital book enriched with narrative texts, full-color illustrations, and culturally contextualized historical content. A limited utilization test showed increased student enthusiasm and improved understanding of historical concepts while fostering appreciation for local cultural heritage through visually engaging materials and meaningful cultural connections. Teachers benefited from the media as both an independent instructional tool and supplementary resource. This study contributes scientifically by providing a structured framework for integrating local oral traditions into digital Islamic Cultural History media using systematic instructional design principles.